Force-Velocity Profiling in Club-Based Field Hockey Players: Analyzing the Relationships between Mechanical Characteristics, Sex, and Positional Demands. - Hicks, Dylan S.; Drummond, Claire; Williams, Kym J.; van den Tillaar, Roland (Journal of Sports Science & Medicine, 2023)
The purpose of this study was to investigate differences between sex and positional demands in club-based field hockey players by analyzing vertical force-velocity characteristics. Thirty-three club-based field hockey athletes (16 males - age: 24.8 ± 7.3yrs, body mass: 76.8 ± 8.2kg, height: 1.79 ± 0.05m; 17 females - age: 22.3 ± 4.2yrs, body mass: 65.2 ± 7.6kg, height: 1.66 ± 0.05m) were classified into two key positional groups (attacker or defender) based on dominant field position during gameplay. Force-velocity (F-v) profiles were established by performing countermovement jumps (CMJ) using a three-point loading protocol ranging from body mass (i.e., zero external mass, 0%) to loads corresponding to 25% and 50% of their own body mass. Across all loads, between-trial reliability of F-v and CMJ variables was determined by intraclass correlation coefficients (ICCs) and coefficient of variation (CV) and deemed to be acceptable (ICC: 0.87 - 0.95, CV% 2.8 - 8.2). Analysis by sex identified male athletes had significantly greater differences in all F-v variables (12.81 - 40.58%, p ≤ 0.001, ES = 1.10 - 3.19), a more enhanced F-v profile (i.e., greater theoretical maximal force, velocity, and power values), plus overall stronger correlations between relative maximal power (PMAX) and jump height (r = 0.67, p ≤ 0.06) when compared to female athletes (-0.71≤ r ≥ 0.60, p = 0.08). Male attackers demonstrated a more 'velocity-oriented' F-v profile compared to defenders due to significant mean differences in theoretical maximal velocity (v0) (6.64%, p ≤ 0.05, ES: 1.11), however differences in absolute and relative theoretical force (F0) (15.43%, p ≤ 0.01, ES = 1.39) led to female attackers displaying a more 'force-oriented' profile in comparison to defenders. The observed mechanical differences identify the underpinning characteristics of position specific expression of PMAX should be reflected in training programmes. Therefore, our findings suggest F-v profiling is acceptable to differentiate between sex and positional demands in club-based field hockey players. Furthermore, it is recommended field hockey players explore a range of loads and exercises across the F-v continuum through on-field and gym-based field hockey strength and conditioning practices to account for sex and positional mechanical differences.